1991
DOI: 10.1084/jem.174.6.1393
|View full text |Cite
|
Sign up to set email alerts
|

CD69-mediated pathway of lymphocyte activation: anti-CD69 monoclonal antibodies trigger the cytolytic activity of different lymphoid effector cells with the exception of cytolytic T lymphocytes expressing T cell receptor alpha/beta.

Abstract: SummaryThe effect of anti-CD69 monodonal antibodies (mAbs) on the induction of the cytolytic activity in different types of lymphoid effector cells has been investigated. Three anti-CD69 mAbs, including the reference mAb MLR3 and two new mAbs (c227 and 31C4), have been used. All cloned CD3-CD16 + natural killer (NK) cells belonging to different subsets (as defined by the surface expression of GL183 and/or EB6 antigens) were efficiently triggered by anti-CD69 mAbs and lysed P815 mastocytoma ceUs in a redirected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(140 citation statements)
references
References 28 publications
(33 reference statements)
4
135
0
1
Order By: Relevance
“…For instance, CD69 is a C-type lectin (Lopez-Cabera et al, 1993) likely to contribute to adhesion and CD38 has been implicated in binding to endothelium (Xu et al, 1994). Furthermore, both CD69 and CD38 are involved in signal transduction and cell activation (Nakamura et al, 1989;Moretta et al, 1991;Tugores et al, 1992;Xu et al, 1994) and CD30, a member of the TNF receptor family, could modulate TIL effector function by interacting with the CD30 ligand in the tumour (Faustman et al, 1982).…”
Section: Tils Display Strong Activation-independent Binding To Endothmentioning
confidence: 99%
“…For instance, CD69 is a C-type lectin (Lopez-Cabera et al, 1993) likely to contribute to adhesion and CD38 has been implicated in binding to endothelium (Xu et al, 1994). Furthermore, both CD69 and CD38 are involved in signal transduction and cell activation (Nakamura et al, 1989;Moretta et al, 1991;Tugores et al, 1992;Xu et al, 1994) and CD30, a member of the TNF receptor family, could modulate TIL effector function by interacting with the CD30 ligand in the tumour (Faustman et al, 1982).…”
Section: Tils Display Strong Activation-independent Binding To Endothmentioning
confidence: 99%
“…It has been shown that NK cells undergo apoptosis through the engagement of Fas molecule by FasL (16,17). Thus, we analyzed whether FasL/Fas interaction was involved in the NK cell death following the binding with tumor targets.…”
Section: Target-induced Nk Cell Apoptosis Is Calcium Dependent and Ismentioning
confidence: 99%
“…The anti-CD16 (NK1, IgG1, VD4, IgG1; KD1, IgG2a) mAb (10) and the anti-CD56 (TA181H12, IgG2a) mAb were obtained, as described (6,14,17,18). The anti-CD3 mAb (Leu4, IgG1), the anti-CD4 mAb (Leu3a, IgG1), the anti-CD8 mAb (Leu2a, IgG1), and the anti-CD56 mAb (Leu19, IgG1) were from BD Biosciences, and the anti-FasL (NOK-1, IgG1) was from BD Pharmingen.…”
Section: Mabs and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations